Keterampilan Mahasiwa Membaca Bahan Perkuliahan di Era Digital - Ristianti, Dina Hajja (CV. Creative Tugu Pena, 2022)
High reading ability is needed in higher education level. In the digital era, the number of digital-based reference books provided by lecturers to convey subject matter, forces students to improve their reading skills to be more effective in learning activities. Although the reference books are intended so that students can study well, not all reference books can be digested well by students. Especially with reading materials outside the scope of learning that are widely available and contain information and interesting content for students, so students are required to plan their reading activities well. The purpose of this study was to see the quality of students' skills in reading lecture materials. This research was conducted with a quantitative descriptive method. The research population is all students of the Guidance and Counseling Study Program of IAIN Curup for the 2021/2022 academic year. The number of samples is 30 people. Data were obtained through a questionnaire. The data were analyzed with the help of SPSS version 16.0 program. The results showed that the quality of students' skills in reading lecture materials in the digital era was in the poor category. Therefore, efforts from all parties and units in universities are needed to improve student skills in the digital era. Keywords: Students Skll, Reading Skill of Students, Digitalization Reading Skill